2020
DOI: 10.1073/pnas.2000100117
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for recognition of RALF peptides by LRX proteins during pollen tube growth

Abstract: Plant reproduction relies on the highly regulated growth of the pollen tube for sperm delivery. This process is controlled by secreted RALF signaling peptides, which have previously been shown to be perceived by Catharanthus roseus RLK1-like (CrRLK1Ls) membrane receptor-kinases/LORELEI-like GLYCOLPHOSPHATIDYLINOSITOL (GPI)-ANCHORED PROTEINS (LLG) complexes, or by leucine-rich repeat (LRR) extensin proteins (LRXs). Here, we demonstrate that RALF peptides fold into bioactive, disulfide bond-stabilized proteins t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(155 citation statements)
references
References 65 publications
7
132
0
Order By: Relevance
“…RALFs and modifies their binding to interaction partners as demonstrated for the CrRLK1L THE1 and its interaction partner RALF34 [20]. Similarly, binding of RALF4 to LRX8 is pH-dependent and stronger under acidic conditions [51]. In vivo and in vitro analyses have shown that dimerization of LRXs is necessary for biological activity [51].…”
Section: Plos Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…RALFs and modifies their binding to interaction partners as demonstrated for the CrRLK1L THE1 and its interaction partner RALF34 [20]. Similarly, binding of RALF4 to LRX8 is pH-dependent and stronger under acidic conditions [51]. In vivo and in vitro analyses have shown that dimerization of LRXs is necessary for biological activity [51].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…It is possible that RALFs present in tobacco support the formation of the LRX1-FER interaction observed in Co-IP experiments and additional RALF1 does not further improve the formation of this protein complex. While the amino acid residues of the LRR domain involved in LRX-RALF interaction have been identified for some LRX/RALF pairs [51], the details on the LRX-FER interaction requires further analyses.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…6B). A cysteine-rich domain (CRD) might act to stabilize the structure of the LRX protein through forming disul de bonds with cysteine residues of the LRR domain (Herger et al, 2019;Moussu et al, 2020). None of the OsLRXs genes except for OsPEX2 has introns (Fig.…”
Section: Phylogenetic Analyses Of Lrxs Family In Rice and Arabidopsismentioning
confidence: 99%
“…Binding RALF peptides to CrRLK1L receptors also involves other interacting partners such as Lorelei-like-Glycosylphosphatidylinositol-Anchored proteins (LLG1,2,3) [9,15] and Leucine-Rich Repeat Extensins (LRX). The latter has been reported to bind RALF4/19 in the pollen tube [16,17] and to interact with FER, as part of cell wall sensing system responsible for vacuolar expansion and cellular elongation [18]. Binding of RALFs to their receptors leads to a number of different intracellular signaling events involving different molecular components, mostly still unidentified.…”
Section: Introductionmentioning
confidence: 99%